Super Wide Band Parabolic Reflector Design With Vivaldi Antenna Array Feed for Switchable Beam Applications - Ozdemiralp, Muhammed Turgut; Turk, Ahmet Serdar; Caliskan, Alper (WILEY, 2025)
In this study, a multi-planar Vivaldi antenna-fed parabolic reflector antenna is presented for wideband applications operating from the L-band to beyond S-band. The proposed antenna is designed for high-gain beam-steering applications in electronic warfare such as surveillance radar, RF jammer transmitter, and drone countermeasure systems. The Vivaldi-type feeder antenna which operates from 550 MHz to 5 GHz (160.3% bandwidth) is fabricated on a low-cost FR4 substrate. Innovative gain enhancement techniques, such as corrugations and directive elements are used in the design. The antenna dimensions are 21 x 23.5 x 0.15 cm, and its standing wave ratio (SWR) remains below 2 along the operating band. The Vivaldi fed parabolic reflector antenna yields 5-24.4 dBi gain of within our frequency range starting from 550 MHz up to 5 GHz. Additionally, beam-steering performance was successfully achieved at +/- 7 degrees angles. The feed array structure is proposed to obtain switchable beam characteristics. The study was validated through full-wave three-dimensional electromagnetic simulations, followed by measurements of the fabricated prototype which is compatible with simulation results.
Keywords: multibeam scan; SWB vivaldi antenna; switchable beam; SURFACE; Engineering; Optics